THE INFLUENCE OF PERCEIVED USEFULL AND PERCEIVE EASE OF USE ON INTEREST IN USING QRIS TRANSACTION SERVICES - Arifin Arifin; Abdul Majid; Jennifer Farihatul Bait (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2025)
PURPOSE - Implementing QRIS as a payment method has encouraged the creation of an integrated payment system through the standardization of payment QR codes. Therefore, it is important to understand how perceived usefulness and ease of use influence people’s interest in QRIS transaction services. This research aims to analyze the influence of these two factors on interest in using QRIS, with the hope of providing valuable insights for developing strategies to increase QRIS adoption in Indonesia.METHODOLOGY - This cross-sectional quantitative research used a survey method to investigate perceptions of benefits and convenience regarding people’s interest in using QRIS, conducted from November 2024 to January 2025, involving people in Indonesia. Respondents were recruited using the accidental sampling method, and a sample of 140 respondents was obtained. The instrument used in this research was a questionnaire; the data obtained was analyzed using SEM PLS 3.0.FINDING - The loading factor measurements were carried out using structural equation modelling (SEM) analysis, and the central construct used in this research is based on the technology acceptance model (TAM). In this research, the PEOU and PU indicators have relatively high coefficient values between 0.892 and 0.954, indicating that these constructs are measured well. Perceived Usefulness is the dominant factor influencing people’s interest in using QRIS. Although Perceice Ease of Use also has potential, it is not significant